INGUINODYINIA - PRESERVATION VERSUS DISSECTION OF THE ILIOINGUINAL NERVE - Jovanovska Spasova, Zanita; Kikerkov, Igor; Pavlovska, Kristina; Slaninka Miceska, Maja; Gruev, Nikola; Arsenkov, Ljuben; Zafirovik, Elena; Elezi, Burim; Saliu, Valon; Fildisevski, Igor; Arsenkov, Stefan; Kipevska, Kristijana; et al. (Journal of Morphological Sciences; Vol 7 No 2 (2024): JMS, 2024)
Inguinal hernia is one of the most common pathologies in the human population and it requires 20 million repairs annually worldwide. Introduction of mesh techniques, after inguinal hernioplasty significantly decreased recurrences.  However inguinodynia, represented by 7-10%,  remains significant problem. Fifty (50) male patients, aged 18-70 y with a diagnosis of unilateral primary inguinal hernia were included in this clinical study, which was designed as a single-blind, randomized and prospective study. Study participants underwent inguinal hernioplasty according to the Lichtenstein method. Patients were randomized into two groups: - group A (25 patients) in which IIN (ilioinguinal nerve) preservation was performed; - group B (25 patients) in which IIN (ilioinguinal nerve) dissection was performed. Postoperatively, the occurrence of pain and its impact on the quality of life was monitored. Fifty (50)  patients were analyzed: 25 in group A and 25 in group B. Inguinodynia was present in a total of two patients, one in each group, i.e. 4%, which indicates that there is no significant difference in the occurrence of inguinodynia in both compared groups. Results of our study indicate absence of significant difference in the occurrence of inguinodynia in the group with preservation and the group with dissection of the IIN. Keywords: inguinodynia, inguinal hernia, mesh techniques.